2010
DOI: 10.1002/aoc.1679
|View full text |Cite
|
Sign up to set email alerts
|

Pd nanoparticles dispersed on solid supports: synthesis, characterization and catalytic activity on selective hydrogenation of olefins in aqueous media

Abstract: Two types of Pd nanoparticle catalysts were prepared having 2-4 nm particle size using silica gel and porous polymer beads as solid supports. 2-Pyridinecarboxaldehyde ligand was anchored on commercially available 3-aminopropyl-functionalized silica gel followed by Pd metal dispersion. Bead-shaped cross-linked poly(4-vinylpyridine-co-styrene) gel was prepared by an emulsifier-free emulsion polymerization of 4-vinylpyridine, styrene and divinylbenzene in the presence of ammonium persulfate and subsequently dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The interaction between support and catalyst can also lead to more reactive materials and allows for much easier recovering and recycling, especially important for rare catalysts, which finally results in the saving of energy. Lim et al [13] have reported that Pd dispersed on SiO 2 is a more efficient catalyst in the hydrogenation of olefins than Pd dispersed on polymer and the former could be recycled more than 10 times without considerable loss in activity. Okumura et al [14] have observed that SiO 2 is a good support for catalytically active metal particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between support and catalyst can also lead to more reactive materials and allows for much easier recovering and recycling, especially important for rare catalysts, which finally results in the saving of energy. Lim et al [13] have reported that Pd dispersed on SiO 2 is a more efficient catalyst in the hydrogenation of olefins than Pd dispersed on polymer and the former could be recycled more than 10 times without considerable loss in activity. Okumura et al [14] have observed that SiO 2 is a good support for catalytically active metal particles.…”
Section: Introductionmentioning
confidence: 99%
“…[13,[19][20][21]. For instance Sai et al [19] have coated noble metals like Au and Ag on amine functionalized SiO 2 nanosprings (helical nanowires), which showed high surface-enhanced Raman spectroscopy activity, useful in sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…11 The 2-pyridinecarboxaldehyde ligand was anchored on commercially available 3-aminopropyl-functionalized silica gel, followed by Pd metal dispersion. Bead-shaped cross-linked poly(4-vinylpyridine-co-styrene) gel was prepared by an emulsifier-free emulsion polymerization of 4-vinylpyridine, styrene, and divinylbenzene in the presence of ammonium persulfate and subsequently dispersing the Pd metal on the synthesized polymer.…”
Section: Hydrogenation Of Alkenesmentioning
confidence: 99%
“…These properties make it possible to use water as a solvent for organic reactions. These solid supports were applied to the syntheses of Pd, Au immobilized heterogeneous catalysts and organic reactions such as hydrogenations, 53 Suzuki–Miyaura couplings, 54,55 Heck–Mizoroki couplings, 56 Sonogashira couplings, 56 Tsuji–Trost reactions, 57 and A-3 coupling reactions 58 that were performed in water. Herein, we wish to demonstrate that our supports can be extended to other metal catalyzed organic reaction applications.…”
Section: Introductionmentioning
confidence: 99%